FE-Aided Synchronization Analysis of Line-Start Synchronous Reluctance Motors - Un-Jae Seo; Dong-Jun Kim; Pil-Wan Han; Yon-Do Chun (Applied Sciences, 2021)
Since line-start synchronous permanent magnet motors (LSPMs) entered the market, they have attracted research interest toward counterpart induction motors of low power-ratings. This paper reports an investigation of line-start synchronous reluctance motors (LS-SynRMs). LS-SynRMs has not been investigated as much as LSPMs have. A motor needs to maximize rotor saliency to achieve high efficiency and a high power-factor. This results in complicated rotor geometry because the rotor cage and multiple flux barriers share the same rotor space. This paper provides an approximate method based on steady state torque analysis by which to estimate the critical inertia of a LS-SynRM. A finite element analysis (FEA)-aided analytical approach to the approximation of steady state torque is proposed to replace the more typical approach based on equivalent circuit parameters. The critical inertia resulting from the proposed method is compared to the results obtained using the FEA.